Mediation effect of trust on the relationship between perception of organization politics and commitment - Setyabudi Indartono (Business Administration Department - Universitas Katolik Parahyangan, 2009)
This paper is the extension study of the relationship between perception of organiza-tion politics (POP), and commitment. This study investigates how trust explained therelation between these relationships. Mediation effect of trust was used to explainhow this perception was related to commitment. Moderation effect was used forfurther explanation on investigation the complexities of these relationships.The result showed that the model was adequacy fit. PoP has negative correlationwith commitment. Trust has fully mediated the relationship between PoP and com-mitment. In order to the moderation, the result showed that employee who has higherof trust was seen stronger POP-Commitment relationship than those who has lowerones.Implication of the findings for organizations and suggestions for future researchare discussed.Keywords: perception of organizational politics, perception of equity, trust, Com-mitment